Advancement in Higher Education: The Role of Marketing in Building Philanthropic Giving Communities - McAlexander,Jim; Koenig,Hal; DuFault,Beth (Journal of Marketing for Higher Education, 2014)
This paper empirically explores ways in which marketers of higher education can contribute to the important task of cultivating alumni philanthropy. Advancement professionals understand that philanthropy is influenced by wealth and affinity. As marketers, we anticipate that our contribution resides with investments in building affinity. Using survey data that measures the affinity of alumni of a large US university that have been commercially screened to reveal individual wealth, this paper provides empirical evidence of the relative contributions of affinity and wealth to giving. Logistic regression analysis reveals that affinity has a greater impact on predicting the likelihood of giving than other variables, including prior-giving and wealth. Important to marketers, this study emphasizes the importance of building affinity and it also uncovers obstacles to affinity formation. This information can be used to bridge and repair alumni relationships with their alma-mater and inform segmented marketing communications to foster alumni enthusiasm for giving.
Keywords: Marketing